Effect of enhanced recovery after surgery (ERAS) protocol on maternal and fetal outcomes following elective cesarean section: an observational trial - Miray Gözde Özdemir; Berrin Gunaydin; Merih Bayram; İbrahim Murat Hirfanoglu (BMC Pregnancy and Childbirth)
Abstract Background We aimed to investigate the maternal, fetal, and neonatal outcomes in parturients scheduled to undergo cesarean section (CS) receiving either standard care or enhanced recovery after surgery (ERAS) protocol. Methods After approval of ethics committee (Gazi University Protocol Record Decision no: 502/31.05.2021) and registry to clinical trials (NCT06753058, Date 12/30/2024) 450 ASA II-III parturients at ≥ 18 years of age scheduled for elective CS under spinal anesthesia using bupivacaine plus opioids were included (n = 150, ERAS group and n = 300, control group). The ERAS protocol included restricting the fasting period before and after the surgery, administering oral nonparticulate carbohydrate solution (25 g of maltodextrin) 2 h (h) before surgery, intraoperative multimodal analgesia under spinal anesthesia and postoperative nausea and vomiting prophylaxis with intravenous (IV) 10 mg metoclopramide + 1.5 mg granisetron; postoperative analgesia was provided with IV nonsteroidal anti-inflammatory drug + paracetamol. While mother-baby contact was provided for both groups, all babies in the ERAS group were encouraged to breastfeed as soon as they were born. Maternal fasting duration, flatus, mobilization, urinary catheter removal times, postoperative visual analogue scale (VAS), rescue analgesic requirement, incidence of postoperative nausea-vomiting (PONV), length of stay (LOS), complications, Turkish version of the Obstetric Quality of Recovery Score 11 (ObsQoR-11T), were recorded in both groups. Newborn demographics, APGAR scores, umbilical cord blood gas analysis, nutritional and breastfeeding status and complications were also recorded. Results In the ERAS group the ObsQoR-11T scores were better than the control group (p < 0.001). Maternal preoperative and postoperative fasting duration, postoperative first flatus and mobilization times and LOS, postoperative VAS, rescue analgesic requirement in the ERAS group were shorter than the control (p < 0.001, p = 0.034, p < 0.001 and p = 0.018, p < 0.001, p < 0.001) and the incidence of PONV was less (p = 0.001). The pH and pO2 were different between the groups. Conclusions We suggest that ERAS use is favorably promising to achieve better maternal recovery in terms of ObsQoR and improved neonatal outcome in terms of nutrition and breastfeeding in the ERAS pathway. Trial registration This study was retrospectively registered to clinical trials (NCT06753058 and published on 12/30/2024, 09:19) according to instructions at https://www.biomedcentral.com/getpublished/editorial-policies#trial+registration .